Integrasi Pembelajaran Budaya Sapaan Jepang melalui Bahasa untuk Meningkatkan Pemahaman Siswa SMA terhadap Keberagaman Budaya - Sakariah, Dewi Saraswati; Widiandari, Arsi (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase high school students' understanding of cultural diversity through Japanese language learning, especially aisatsu (greeting) material. The activity was carried out at SMA Negeri 1 Semarang as part of the "Himawari Goes to School" program which involved collaboration between lecturers and students. The material presented includes various types of greetings in Japanese, such as greetings during meetings, farewells, as well as special greetings such as apologies (sumimasen, gomenasai), which are accompanied by the practice of ojigi (bowing) as a form of nonverbal respect. Through exposure, simulation, and discussion methods, students are invited to understand the social context behind the use of these greetings. The results of the activity showed that students were able to differentiate the use of aisatsu based on the situation and the relationship between speakers, and showed increased awareness of Japanese cultural values. This activity proves that the integration of language and culture learning can be an effective tool in fostering tolerance and appreciation for cultural diversity among students.